Algebra-1 Problems

6.7 Principle of Zero Products


Problem #

Problem Statement

Problems Similar To

1.

Solve for x

\begin{equation}(x-4)(x-9)=0\end{equation}

2.

Solve for x

\begin{equation}2(x-3)x=0\end{equation}

3.

Solve for x

\begin{equation}(6x-1)(x-8)=0\end{equation}

4.

Solve for x

\begin{equation}(2x+2)(2x-2)=0\end{equation}

5.

Solve for x

\begin{equation}(5x-5)(x-10)=0\end{equation}

6.

Solve for x

\begin{equation}x^{2}+12x+27=0\end{equation}

7.

Solve for x

\begin{equation}x^{2}=(-11)x-24\end{equation}

8.

Solve for x

\begin{equation}x^{2}+14x+49=0\end{equation}

9.

Solve for x

\begin{equation}25x^{2}-4=0\end{equation}

10.

Solve for x

\begin{equation}-(x^{2}+4x-21)=0\end{equation}

11.

Solve for x

\begin{equation}(-4)(x^{2}+5x-14)=0\end{equation}

12.

Solve for x

\begin{equation}6x^{2}+23x+10=0\end{equation}

13.

Solve for x

\begin{equation}-(x^{2}+62x-56)=0\end{equation}

14.

Solve for x

\begin{equation}5(6x^{2}+15x-42)=0\end{equation}

15.

Solve for x

\begin{equation}2(x^{2}-100)=0\end{equation}

16.

Solve for x

\begin{equation}6(49x^{2}+84x+36)=0\end{equation}

17.

Solve for x

\begin{equation}9x^{2}=4\end{equation}

18.

Solve for x

\begin{equation}(-4)(x^{2}-8x+16)=0\end{equation}

19.

Solve for x

\begin{equation}49x^{2}-14x+1=0\end{equation}

20.

Solve for x

\begin{equation}2(9x^{2}+6x+1)=0\end{equation}

21.

Solve for x

\begin{equation}2(81x^{2}-18x+1)=0\end{equation}

22.

Solve for x

\begin{equation}5(x^{2}+10x+25)=0\end{equation}

23.

Solve for x

\begin{equation}36x^{2}=(\frac{2}{1})^{2}\end{equation}